Istri sebagai Pencari Nafkah Utama: Studi Normatifitas Hukum Islam dan Urusan Domestik di Kelurahan Loa Bakung - Kamsiah, Kamsiah; Fajriyyah, Latifatul (Lembaga Penelitian dan Pengabdian kepada Masyarakat, UIN Sultan Aji Muhammad Idris Samarinda, 2022)
This study aims to: (1) Find out how the portrait of the wife in Loa Bakung replace the husband's duties in earning a living. (2) Knowing how the role of husbands who replace the wife's duties in taking care of the household. (3) Knowing how Islamic law views the role of the wife taking over the husband's duty as the breadwinner. This study uses a qualitative approach. The object of this research is purposive sampling, namely several husbands and wives aged 40-65 years which are carried out by their wives in fulfilling their livelihood for their families. The data were then analyzed by descriptive-analytic method using a review of Islamic Law. This study shows that the husband as a leader is obliged to earn and provide for his family, but due to various reasons such as reduction of employees, the closure of the company, the ability factor that make husbands no longer work can be productive again. So that the wife have to replace her husband in earning a living to meet the needs of her family. In a situation like this, the husband should not actually force the wife to spend her income for household needs, because the husband's obligation to provide a living. There is no way out for the wife except to surrender to the situation as an effort to maintain the integrity of the household.